AGE RELATIONSHIP OF BREAST MILK COMPANION FOOD WITH STUNTING INCIDENTS IN SELOJARI VILLAGE - Laily Himawati; Dhiyan Nany Wigati; Maratul Azizah (Lppm Unan, 2022)
Background: Based on riskesdas in 2018 The average prevalence of stunting toddlers in Indonesia in 2005-2017 was 36.4%. In 2018, 100 districts in 34 provinces were designated as priority locations for stunting reduction. This number will increase by 60 counties in the following year. Based on Rakernas 2020 data, the number of stunting toddlers in Indonesia reached 27.7% while one of the targets for the direction and policy of the National Medium Term Development Plan (RPJMN) in 2020-2024 is to increase quality and competitive human resources, one of which includes efforts to accelerate nutritional improvements in handling stunting, and targets that in 2024 the stunting rate in Indonesia will decrease to 14% (Rakernas. 2020). Method: Using cross sectional is done in Selojari Village. Sampling was carried out in multistage random sampling with a large sample of 52 mothers-toddlers. The observed free variable age of Breastmilk companion food administration consisting of the age of the first time given food, while the dependent variable is the incidence of stunting. The data analysis used is the chi-square test. Results: The results of bivariate analysis showed that the first time mp-breast milk administration was significantly related to stunting events. Conclusion: The conclusion of this study is that there is an age relationship between mpasi administration and stunting events.